2020
DOI: 10.1186/s13104-020-05008-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing left ventricular ejection fraction in patients with coronary microvascular disease and obstructive coronary artery disease

Abstract: The aim of our research was to evaluate the relationship involving left ventricular ejection fraction, low density lipoprotein, B-type natriuretic peptide, Troponin I and coronary flow reserve, and to determine the predictors of left ventricular ejection fraction in patients with coronary microvascular disease and obstructive coronary artery disease, and in patients with coronary microvascular disease. Results: The mean age was 58.5 ± 12.5 years. In patients with obstructive coronary disease and coronary micro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…19 The relationship between coronary slow flow and low ejection fraction is complicated and multifaceted, involving coronary microvascular dysfunction, coronary artery disease, and their impact on left ventricular function. 20 Although some studies have not identified a statistically significant relationship between traditional cardiovascular risk factors and the coronary slow flow phenomenon, others have pointed out the association of atherosclerosis, vascular spasm, and microvascular dysfunction with the CHA2DS2-VASc score, which is commonly used to assess risk for stroke. 21,22 Complete blood cell count components have been demonstrated to be a valid and easily available predictor of cardiovascular events, especially among patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…19 The relationship between coronary slow flow and low ejection fraction is complicated and multifaceted, involving coronary microvascular dysfunction, coronary artery disease, and their impact on left ventricular function. 20 Although some studies have not identified a statistically significant relationship between traditional cardiovascular risk factors and the coronary slow flow phenomenon, others have pointed out the association of atherosclerosis, vascular spasm, and microvascular dysfunction with the CHA2DS2-VASc score, which is commonly used to assess risk for stroke. 21,22 Complete blood cell count components have been demonstrated to be a valid and easily available predictor of cardiovascular events, especially among patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…The left ventricular ejection fraction (LVEF) and 2 years of survival following an AMI has been predicted independently by using the values of cardiac biomarker NT-proBNP which was estimated approximately 2 to 4 days after the event. [10][11][12] There is a rapid rise in the levels of NT-proBNP over the first 24 hours after acute myocardial infarction which then tends to stabilize. After AMI the elevated levels of NT-proBNP was useful in identifying patients at risk for heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Mayala et al showed a negative correlation between left ventricular ejection fraction and serum LDL cholesterol levels. 18 The limitation of this study was that it was conducted in a single tertiary care centre. Multi-centre studies with larger sample sizes are needed to be more conclusive.…”
Section: Discussionmentioning
confidence: 99%